Integrating shade provision into the healthy built environment agenda: the approach taken in NSW, Australia - Elizabeth L King; Susan Thompson; Nicola Groskops (Sax Institute, 2022)
Objective: To detail the approach and progress being made by the Shade Working Goup (SWG) across health and the built environment to embed natural and built quality shade provision in places used by the community in New South Wales (NSW), Australia. Type of program or service: The NSW Skin Cancer Prevention Strategy sets a comprehensive and collaborative approach to skin cancer prevention for the state of NSW. Through the Strategy, the SWG has been promoting the benefits of shade for solar ultraviolet radiation (UVR) protection, in addition to heat mitigation, among peak bodies, governments and practitioners. Findings: With representation from health- and built environment-related disciplines, the SWG has set the foundations for raising awareness, as well as delivering education and advocacy initiatives to deepen engagement and generate evidence to better inform healthy built environment practice. Lessons learnt: The ways of working adopted by the SWG demonstrate effective collaborative principles for others to use to positively impact accepted practice across health and the built environment.